Modification of aviation gasoline with aliphatic alcohols additives: an analytical review of prospects. (2015) - Boichenko, Sergii; Lejda, Kazimierz; Lychmanenko, Olesya; Boichenko, Mariya; Reshetilowski, Volodymyr
The paper presents the results of analysis of the regulations of the traditional aviation fuels quality. The content of antiknock additives in these fuels has been established in the investigated fuels. The influence of aliphatic alcohols on operational, physical and chemical and environmental properties of traditional petroleum aviation fuels has been studied. The research has also investigated the use of ethyl, methyl and butyl alcohols in motor-car fuel systems in the composition of complex and pure alternative fuels in aviation. It has been confirmed that addition of aliphatic alcohols to traditional aviation fuels enables reduction of harmful emissions in the upper layers of the atmosphere. Alcohol-containing petrol is being enriched with oxygen, which enables more complete combustion of fuel and lessens emissions of carbon oxides.